Mystification as an Artistic Strategy in Milan Kundera's Work. (3rd July 2018) - Čulík, Jan
ABSTRACT: Using close reading of Kundera's texts, Jan Čulík argues that many arguments in Milan Kundera's literary works are deliberate provocations. Kundera's approach is undoubtedly related to post-modernism, although he used his mystification techniques long before the arrival of postmodernism, as early as in the Stalinist 1950s when he published fake quotes from Lenin in official Stalinist publications. In Jan Čulík's view, it is the purpose of Milan Kundera's systematic use of false facts, distortions and disrupted logic to warn his readers against against the unreliability of words and human communication. Kundera seems to argue that the world in its complexity is basically unknowable and the only thing that is left for us is, in despair, in our ignorace of what is going on around us, to carry out pranks.